Cr(salen) catalysed asymmetric ring opening reactions of epoxides in room temperature ionic liquids - Song, CE; Oh, CR; Roh, EJ; Choo, DJ (ROYAL SOC CHEMISTRY, 2000)
Cr(salen) catalysed asymmetric ring opening reactions of epoxides with TMSN3 proceed readily in the room temperature ionic liquid 1-butyl-3-methylimidazolium salts ([bmim][X]) with easy catalyst/solvent recycling.
Keywords: 1,2-AMINO ALCOHOLS; EFFICIENT; SOLVENTS; COMPLEXES